Two Populations of Mites (Tyrophagus putrescentiae) Differ in Response to Feeding on Feces-Containing Diets - Hubert, Jan; Nesvorna, Marta; Sopko, Bruno; Smrz, Jaroslav; Klimov, Pavel; Erban, Tomas (Frontiers in Microbiology, 2018)
BACKROUND: Tyrophagus putrescentiae is a ubiquitous mite species occurring in the soil, stored products and house dust, infesting food and causing allergies to people. Tyrophagus putrescentiae populations harbor different bacteria communities ranging from intracellular symbionts and gut bacteria. Spreading microorganisms via fecal pellets is a possibility, which has not been studied in much detail yet. This may be in an important way for gut bacteria to colonize next generations of mites. In the soil the feces could be a mechanism of spreading of microorganisms. METHODS: Extracts from used mite culture medium (i.e. residual food, mite feces and dead mite bodies) were used as a source of feces-inhabiting microorganisms and the food the mites. Two Tyrophagus putrescentiae populations (L and P) were used for experiments, they hosted the intracellular bacteria Cardinium and Wolbachia, respectively. The effect of the fecal fraction presence on the respiration in a mite microcosm, mite fitness and microbiome composition was evaluated. RESULTS: Feces from P-population contained more than 90% of Bartonella-like sequences. L-population feces had Staphyloccocus, Virgibacillus, Brevibacterium, Enterobacteriaceae, and Bacillus. The mites from P-population, but not L-population, increased bacterial respiration in microcosms in comparison to no-mite controls. Both L- and P-feces extracts had an inhibitory effect on the respiration of the microcosms, indicating antagonistic interactions inside feces-associated bacteria. The mite micirobiomes were resistant to acquire new bacterial species from the feces, but their bacterial profiles were affected. Feeding of P-mites on P-feces-enriched diets resulted in an increase of Bartonella abundance from 6 to 20% of the total bacterial sequences and a decrease of Bacillus abundance. The population growth was 5-folds accelerated on P-feces extracts in comparison to the control. CONSLUSION: The mite microbiome, to a certain extent, resists the acquisition of new bacteria, when mites are feed on the feces of the same species. However, Bartonella-like bacteria-feces-enriched diet seems to be beneficial for mite populations with symbiotic Bartonella-like bacteria. The coprophagy on own population feces could be a mechanisms of bacterial acquisition in Tyrophagus putrescentiae.